2006
DOI: 10.1016/j.febslet.2006.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor receptors in helminth parasites: Signalling and host–parasite relationships

Abstract: Parasitic helminths remain major pathogens of both humans and animals throughout the world. The success of helminth infections depends on the capacity of the parasite to counteract host immune responses but also to exploit host-derived signal molecules for its development. Recent progress has been made in the characterization of growth factor receptors of various nematode and flatworm parasites with the demonstration that transforming growth factor beta (TGF-b), epidermal growth factor (EGF) and insulin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…D ifferent studies have demonstrated that the development of S. mansoni could be dependent on host hormones (De Mendonca et al, 2000) and growth factors (Dissous et al, 2006) but the possibility that insulin-dependent mechanisms also occur in schistosomes has been extensively debated. Indeed, the first studies showing that insulin could increase oxygen and glucose uptake, life span and resistance to antibodies of schistosomula (Levi-Schaffer & Smolarsky, 1981) have been further disapproved by other authors who concluded to an insulin independence of schistosomes (Clemens & Basch, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…D ifferent studies have demonstrated that the development of S. mansoni could be dependent on host hormones (De Mendonca et al, 2000) and growth factors (Dissous et al, 2006) but the possibility that insulin-dependent mechanisms also occur in schistosomes has been extensively debated. Indeed, the first studies showing that insulin could increase oxygen and glucose uptake, life span and resistance to antibodies of schistosomula (Levi-Schaffer & Smolarsky, 1981) have been further disapproved by other authors who concluded to an insulin independence of schistosomes (Clemens & Basch, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Convincing studies have demonstrated the importance of protein kinases in schistosome growth and development (Dissous et al 2006, Knobloch et al 2007, Beckmann et al 2010a. The effect of anti-cancer drugs on the reproductive activity of parasites as well as on their survival in in vitro culture (shown recently for the Abl-kinase inhibitor Imatinib by Beckmann and Grevelding 2010) reinforces the hypothesis that parasite protein kinases could represent new targets for antischistosomal strategies, but also that piggy-backing cancer drugs for treatment of schistosomiasis is really worth considering (Dissous and Grevelding 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR), a tyrosine kinase receptor, is another example of growth factor receptors that are expressed on the surface of parasites (Ramachandran, et al, 1996) and has been shown to respond to human EGF (Vicogne, et al, 2004). The role of host factors in schistosome development has been reviewed (Davies and McKerrow, 2003, Dissous, et al, 2006, Escobedo, et al, 2005, Knobloch, et al, 2007.…”
Section: Signals From Host Environmentmentioning
confidence: 99%